2000
DOI: 10.1097/00007890-200003150-00038
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolic Acid-Induced GTP Depletion Also Affects Atp and Pyrimidine Synthesis in Mitogen-Stimulated Primary Human T-Lymphocytes1

Abstract: MPA affects pyrimidine as well as purine responses to mitogens in T-lymphocytes, but not in an integrated way. The molecular mechanisms underlying these disproportionate changes can best be explained by MPA-related inhibition of amidophosphoribosyltransferase, catalysing the first step in purine biosynthesis. This would increase phosphoribosylpyrophosphate availability, thereby stimulating UTP biosynthesis. Such imbalances, coupled with ATP-depletion, could underlie reported side effects and might be overcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
30
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 28 publications
5
30
0
Order By: Relevance
“…Similarly, it has been previously demonstrated that brequinar, an inhibitor of de novo pyrimidine synthesis, suppresses not only T cell proliferation, but also IL-2 receptor expression (22). The inhibition of mRNA synthesis because of the decrease in ATP, induced by either MMF or brequinar, may explain the suppression of CD25 expression (23,24). The fact that we only observed a rather weak inhibition of CD25 expression only at high MPA concentrations provides some circumstantial evidence for the utility of an additional anti-CD25 monoclonal antibody to sufficiently suppress acute rejection…”
Section: Discussionmentioning
confidence: 84%
“…Similarly, it has been previously demonstrated that brequinar, an inhibitor of de novo pyrimidine synthesis, suppresses not only T cell proliferation, but also IL-2 receptor expression (22). The inhibition of mRNA synthesis because of the decrease in ATP, induced by either MMF or brequinar, may explain the suppression of CD25 expression (23,24). The fact that we only observed a rather weak inhibition of CD25 expression only at high MPA concentrations provides some circumstantial evidence for the utility of an additional anti-CD25 monoclonal antibody to sufficiently suppress acute rejection…”
Section: Discussionmentioning
confidence: 84%
“…Other studies of Con A-stimulated human T lymphocytes show that MPA induces GTP depletion and decreases ATP pools, resulting in a lack of pyrimidine synthesis (29).…”
Section: Pharmacodynamics Of Mycophenolate Mofetilmentioning
confidence: 95%
“…Blockade of IMPDH by MPA was shown to deplete the guanosine (Gua) pool in lymphocytes (6) and to inhibit T and B cell proliferation, differentiation of alloreactive cytotoxic T cells, and Ab responses (7)(8)(9). More recently, MMF was shown to impair maturation of murine dendritic cells, suggesting that MMF can also affect APC functions (10).…”
Section: Ycophenolate Mofetil (Mmf)mentioning
confidence: 99%
“…More recently, MMF was shown to impair maturation of murine dendritic cells, suggesting that MMF can also affect APC functions (10). Inhibition of T lymphocyte proliferation was shown to result from a blockade of activated lymphocytes in early-to mid-G 1 phase of the cell cycle, resulting from a lack of induction of cyclin D/cyclin-dependent kinase (CDK) 6 and impaired degradation of the CDK inhibitor p27 Kip1 (9). Downregulation of the CDK inhibitor p27 Kip1 was shown to depend on the binding of IL-2 to its high-affinity trimeric receptor (11)(12)(13).…”
Section: Ycophenolate Mofetil (Mmf)mentioning
confidence: 99%